PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA PADA BALAI DIKLAT LINGKUNGAN HIDUP DAN KEHUTANAN PEMATANGSIANTAR - Nina Arsilah; Darwin Lie; Marisi Butarbutar; Lora Ekana Nainggolan (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
The formulation of this research problem is how the influence of Leadership and Job Satisfaction on Work Discipline at Balai Diklat Lingkungan Hidup dan Kehutanan Pematangsiantar. The research method used in this paper is literature research and field research. Its population is employees of Balai Diklat Lingkungan Hidup dan Kehutanan Pematangsiantar amounted to 57 people. The data used are data by qualitative and qualitative data, and data collection techniques by questionnaire, interview and documentation. Then the technique of data analysis using qualitative descriptive method and quantitative descriptive method. Results of analysis of multiple linier regression is Ŷ = 26,243 + 1,232X1 + 0,681X2, means there is a positive influence between leadership and job satisfaction on work discipline. The strength of the relationship between the three variables is strong, is r = 0,752. From the coefficient of determination can be explained high low work discipline 56,5%, and the remaining 43,5% explained by other factors that are not discussed in this study. From the results of processing and calculation of the questionnaire, the authors get the conclusion that the leadership and job satisfaction applied Balai Diklat Lingkungan Hidup dan Kehutanan Pematangsiantar have a positive and significant effect on work discipline. This is proven by hypothesis testing simultaneously, where the test result fhitung (35,062)> fhitung (3,17) with significance level 0,000 < alpha 0,05. Keywords: Leadership, Job Satisfaction And Work Discipline